SER analysis of cooperative M2M communications assisted by multiple AF relays - Nan ZHANG; Feng-kui GONG; Jian-hua GE (Tongxin xuebao)
For the mobile-to-mobile (M2M) communication assisted by multiple mobile amplify-and-forward (AF) relays (MAF-M2M),the lower bound of SER with M-PSK was derived by using the MGF approach,where a gen lized cascaded Nakagami-m channel model was used to provide a realistic description of the M2M channel.A more asymptotic SER expression was also derived by combining with an approximated PDF method.It was shown that the performance of M2M communication systems over channels with different parameter m can be obviously improved if AF relays are used.The simulated SER curves prove the rightness of the derived lower bound and approximated SER expressions.